The impact of tax uncertainty on irreversible investment - Rainer Niemann (Arbeitskreis Quantitative Steuerlehre (arqus), 2006)
Traditional models of capital budgeting including taxes are based on deterministic tax rates and tax bases. In reality, however, there are multiple sources of tax uncertainty. Tax reforms induce frequent changes in both tax rates and tax bases, making future taxation of investments a stochastic process. Fiscal authorities and tax courts create additional tax uncertainty by interpreting current tax laws differently. Apart from fiscal tax uncertainty, there is modelspecific tax uncertainty, because investors use simplified models for computing an investment project's tax base and anticipate the actual tax base incorrectly. I analyze the effects of stochastic taxation on investment behaviour in a real options model. The potential investor holds an option to invest in an irreversible project with stochastic cash flows. To cover the combined effects of tax base and tax rate uncertainty, the investment's tax payment is modelled as a stochastic process that may be correlated with the project's cash flows. I show that increased uncertainty of tax payments has an ambiguous impact on investment timing. Thus, the popular view that tax uncertainty depresses real investment can be rejected. For low tax uncertainty, high cash flow uncertainty and high correlation of cash flows and tax payment, increased tax uncertainty may even accelerate investment. A higher expected tax payment delays investment. Surprisingly, a higher tax rate on interest income affects investment timing ambiguously.
Keywords: 330; Betriebliche Investitionspolitik; Investition; Realoption; Irreversibility of Investment; Steuer; Risiko; Theorie